Return to sport from viral myocarditis in a previously healthy collegiate athlete: a case report - Wirtz, A. (Journal of Athletic Training, 2023)
The objective of this paper is to present the case of a healthy, 19-year-old female collegiate soccer player who developed acute pulmonary edema and acute heart failure in the recovery room after hip labral arthroscopic surgery. The patient's initial diagnosis, of negative pressure pulmonary edema in direct relation to extubation, was questioned when she became hemodynamically unstable. A cardiac biopsy revealed acute pulmonary edema and heart failure secondary to viral myocarditis. The patient was treated and discharged 10 days after admission. Specific and substantiated return-to-play guidelines after a cardiac event, specifically viral myocarditis, have been sparse. The interprofessional collaboration between athletic trainers and cardiologists is a key dynamic in the clinical decision-making process of a safe return to competitive athletic participation after a cardiac event.